Coronectomy of two neighbouring ankylosed mandibular teeth – A case report - Biočanin, Vladimir; Todorović, Ljubomir (Vojnosanitetski pregled, 2014)
Introduction. Intentional partial odontectomy or coronectomy is primarily advocated in situations with intimate relationships between the roots of the tooth indicated for extraction and the inferior alveolar nerve (IAN). The aim of this report was to present a patient with two neighbouring infraoccluded teeth in the right mandible indicated for extraction prior to prosthetic rehabilitation, which were coronectomied as to prevent injuring of the IAN and causing iatrogenic fracture of the mandibular body. Case report. Coronectomy of both teeth was performed as recommended in the literature. The patient had no special discomfort after the operation or deficit in sensitive nerve function, and the wound healed uneventfully. The patient was followed regularly during a 2- year period. Conclusion. The presented case suggests coronectomy as quite beneficial solution for avoiding serious problems (injuring of the IAN and possible fracture of the mandible) and making feasible forthcoming prosthetic rehabilitation.
Keywords: tooth ankylosis; mandible; oral surgical procedures; treatment outcome